ANALYSIS OF PUBLIC HEALTH INSURANCE PROGRAM, PERFORMANCE-BASED CAPITATION AND SERVICE QUALITY ON PATIENT SATISFACTION OF LEVEL I SERVICE FACILITIES IN NGANJUK REGENCY - Panjaitan, Biller; Laili Rahmiyati, Ayu; Vidiarti, Yunlia (Universitas Islam Lamongan, 2024)
The Nganjuk District General Hospital is one of the health facilities that BPJS refers to. Several obstacles are still found related to health services to patients related to the implementation of the health insurance program, then there are several changes related to performance-based capitation which have an impact on patient satisfaction who need good service with adequate facilities.The aim of this research is to determine the effect of health insurance programs, performance-based capitation and service quality on patient satisfaction at level I health facilities in Nganjuk district. The method used by researchers in carrying out this research is multiple linear regression analysis. This analysis was chosen because the researcher used more than 1 (one) independent variable used by the researcher. The data collection technique used by researchers to obtain primary data was by using a questionnaire for 67 respondents. The results of the research show that there is a partially negative and significant influence of the health insurance program on patient satisfaction at level 1 health facilities in Nganjuk district. There is a positive and significant effect of performance-based capitation on patient satisfaction at level 1 health facilities in Nganjuk district. There is a positive and significant influence of service quality on patient satisfaction at level 1 health facilities in Nganjuk district, then simultaneously there is a significant influence of the health insurance program, performance-based capitation and service quality on level 1 health facilities in Nganjuk district